A novel approach in revealing mechanisms and particular step predictors of pH dependent tartrazine catalytic degradation in presence of Oxone®. (October 2021) - Popadić, Marko G.; Marinović, Sanja R.; Mudrinić, Tihana M.; Milutinović-Nikolić, Aleksandra D.; Banković, Predrag T.; Đorđević, Ivana S.; Janjić, Goran V.
Abstract: The degradation of tartrazine in the presence of cobalt activated Oxone® (potassium peroxymonosulfate) was investigated at different initial pH values. Aluminum pillared clay had the role of a support for catalytically active cobalt oxide species. The degradation of tartrazine and the formation of a mixture of degradation products were monitored using the Ultraviolet–Visible (UV–Vis) spectroscopy and gas chromatography–mass spectrometry (GC-MS). The exact qualitative composition of this mixture and the determination of the most probable mechanism of degradation (the primary goal) were obtained using GC-MS. Besides, the main reaction pathway (reaction with SO4 ˙ˉ radical anion) and secondary pathways were proposed depending on the pH value. At pH = 6 the reaction with HO˙ radical was proposed. At pH = 11 decarboxilation was suggested as the first step of the secondary proposed reaction pathway. The combination of results acquired from the deconvolution of UV–Vis spectra and the theoretical UV–Vis spectra of degradation products, whose occurrence was predicted by quantum-chemical calculations, was proven to be beneficial for the identification of tartrazine degradation products and for defining UV–Vis predictors of particular degradation steps. An additional contribution of this paper, from the reactivity aspect, was the establishment of the critical structural demand for the radical degradation of any diazo compound. The existence of a hydrogen atom bound to a diazo group was found to be the essential prerequisite for the radical cleavage of diazo compounds. Graphical abstract: Image 1 Highlights: Co 2+ impregnated pillared clay was tested as catalyst in presence of SO4 ˙ˉ radical. Uv–Vis spectroscopy, GC-MS and DFT calculations were used to determine pH influence. Predictors of mechanisms of pH dependent tartrazine degradation were established. Besides main reaction pH dependent different competitive paths were proposed. H atom bonded to diazo group is essential for radical cleavage of diazo compounds.